Genetic Susceptibility to Antisynthetase Syndrome Associated With Single-Nucleotide Variants in the IL1B Gene That Lead Variation in IL-1β Serum Levels - Ponce-Gallegos, Marco Antonio; Ramos-Martínez, Espiridión; García-Carmona, Adriana; Mejía, Mayra; Nava-Quiroz, Karol J.; Pérez-Rubio, Gloria; Ambrocio-Ortiz, Enrique; González-Pérez, Montserrat I.; Buendía-Roldán, Ivette; Rojas-Serrano, Jorge; Falfán-Valencia, Ramcés (Frontiers in Medicine, 2020)
The antisynthetase syndrome (ASSD) is an autoimmune disorder characterized by myositis, arthritis, mechanic's hands, fever, Raynaud phenomenon, and interstitial lung disease (ILD). We aimed to evaluate single-nucleotide polymorphisms in the interleukin 1B (IL1B) gene and their association between ILD with antisynthetase autoantibodies, as well as IL-1β serum levels. The most frequent antisynthetase autoantibody was anti-Jo1. The most frequent tomographic pattern was non-specific interstitial pneumonia, whereas in the anti-Jo1 subjects, it was organized pneumonia. Anti-Jo1 patients tend to have more significant arthritis, and Raynaud phenomenon have higher levels of creatinine phosphokinase. In the IL1B gene, the GG genotype and G allele of rs1143634 [odds ratio (OR) = 2.21 and OR = 2.60, respectively, p < 0.05] are associated with an increased risk, as well as with the dominant and recessive models (p < 0.05). This finding is maintained after logistic regression analysis adjusting for potential confounding variables (p < 0.05). Subjects with the rs16944/AG heterozygous genotype had higher serum levels of IL-1β compared to homozygous (p < 0.05). In conclusion, rs1143634 is associated with a higher risk of ASSD. Also, the GA genotype is associated with higher levels of IL-1β in ASSD patients.